Polymer as banknotes / Norhidayah Ismail - Ismail, Norhidayah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Each country has its currency that represents the country. Some countries use the same currency for their daily monetary transactions. For instance, Malaysia uses the Ringgit Malaysia (RM) for its monetary transactions. Ringgit Malaysia comes in the form of paper banknotes and coins. Since 2004, Bank Negara Malaysia has replaced the RM5 paper banknotes with RM5 polymer banknotes in circulation. The design, colour, and size remained the same as the old RM5 paper banknotes, but enhanced security features were added to the new polymer banknotes.